1970
DOI: 10.1042/bj1160035
|View full text |Cite
|
Sign up to set email alerts
|

The formation of short fibres from native cellulose by components of Trichoderma koningii cellulase

Abstract: Cellulolytic enzyme components of culture filtrates of Trichoderma koningii were fractionated on ionic and non-ionic forms of Sephadex and on cellulose powder (Whatman) and examined for their ability to hydrolyse soluble carboxymethyl-cellulose, and to saccharify, solubilize and form short fibres from native undegraded cellulose of the type found in cotton. DEAE-Sephadex provided two CM-cellulase components and a C(1) component; the C(1) component acted weakly and solely on cotton, forming soluble products but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
2

Year Published

1981
1981
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 8 publications
2
27
2
Order By: Relevance
“…Increased cellulose accessibility during enzymatic hydrolysis has been attributed to many factors. These include H 2 O 2 production in the presence of Fe ion (Koenigs, 1975), or the shortfiber-forming factor in filtrates of T. koningii (Halliwell and Riaz, 1970), or T. reesei CBH1 (Chanzy et al, 1983;Lee et al, 2000) or its catalytic domain (Lee et al, 1996) or the CBH2 catalytic domain (Woodward et al, 1992), T. reesei endoglucanase -exoglucanase complex (Sprey and Bochem, 1993), Humicola insolens CBH2 (Boisset et al, 2000), Thermomonospora fusca cellulases E3 and E5 (Walker et al, 1990, some noncatalytic domains of cellulase such as the CBM of C. fimi endoglucanase A (Din et al, 1991(Din et al, , 1994, a short fiber-generating polypeptide from T. pseudokoningii (Wang et al, 2003), a T. reesei fibril-forming protein (MW = 11.4 kD) (Banka et al, 1998), and a novel T. reesei protein called swollenin (MW = 49 kD) (Saloheimo et al, 2002).…”
Section: Cellulose Hydrolysis On the Mechanism Of Cellulose Hydrolysimentioning
confidence: 99%
“…Increased cellulose accessibility during enzymatic hydrolysis has been attributed to many factors. These include H 2 O 2 production in the presence of Fe ion (Koenigs, 1975), or the shortfiber-forming factor in filtrates of T. koningii (Halliwell and Riaz, 1970), or T. reesei CBH1 (Chanzy et al, 1983;Lee et al, 2000) or its catalytic domain (Lee et al, 1996) or the CBH2 catalytic domain (Woodward et al, 1992), T. reesei endoglucanase -exoglucanase complex (Sprey and Bochem, 1993), Humicola insolens CBH2 (Boisset et al, 2000), Thermomonospora fusca cellulases E3 and E5 (Walker et al, 1990, some noncatalytic domains of cellulase such as the CBM of C. fimi endoglucanase A (Din et al, 1991(Din et al, , 1994, a short fiber-generating polypeptide from T. pseudokoningii (Wang et al, 2003), a T. reesei fibril-forming protein (MW = 11.4 kD) (Banka et al, 1998), and a novel T. reesei protein called swollenin (MW = 49 kD) (Saloheimo et al, 2002).…”
Section: Cellulose Hydrolysis On the Mechanism Of Cellulose Hydrolysimentioning
confidence: 99%
“…Recent work has demonstrated that rapid fiber fragmentation at the very early stages of hydrolysis leads to a dramatic reduction in slurry viscosity, which alleviates some of the issues associated with high solids hydrolysis (2). It has been suggested that fiber fragmentation is primarily induced by the endoglucanase family of enzymes (3,4), although other proteins present in the cellulolytic mixture, such as the more recently characterized oxidative enzymes (5,6) and amorphogenesis-inducing proteins (7)(8)(9), have also been shown to contribute to the overall deconstruction process.…”
mentioning
confidence: 99%
“…Tamarind seed xyloglucan (Glyloid 3s) was obtained from the Dainippon Pharmaceutical Corporation, Osaka, and purified as before (Fanutti eta/., 1991). Digests were carried out at 30°C in 50 mM ammonium acetate buffer pH 5.0, using 8.3 mU 'cellulase' or 8.3 k g nasturtium endoglucanase protein ml-', and followed by monitoring both the reducing power (Halliwell and Riaz, 1970) and the viscometric flow-time (Edwards eta/., 1986) of the solution.…”
Section: Methodsmentioning
confidence: 99%
“…Reaction progress was monitored by measuring reducing power (Halliwell and Riaz, 1970) by HPLC and by TLC.…”
Section: Enzyme Digestion Of Oligosaccharides D To H and Their Alditolsmentioning
confidence: 99%